Peningkatan Kemandirian Lansia Melalui Okupasi Terapi dan Psychotheraphy di Panti Sosial Tresna Werdha Sicincin Padang Pariaman - Renidayati Renidayati; N Rachmadanur (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2022)
The increasing number of elderly causes complex problems for the elderly, families and communities. Physiological and motor changes make the elderly feel useless, demotivated and withdraw from the environment so that the need for attention becomes excessive. These changes greatly affect the independence of the elderly. This study aims to determine changes in the independence of the elderly before and after occupational therapy and group psychotherapy at the Tresna Werdha Sabai Nan Aluih Sicincin Nursing Home, Padang Pariaman Regency. The research used Quantitative research with “Quasi Experimental pre and post test with control group with 63 elderly people as respondents. The sampling was taken purposively. The research instrument used the Katz AD Index. The data analysis used Paired sample t-test and Independent t-test. The results showed that there were differences in the independence of the elderly before and after being given Occupational therapy modified with Group Psychotherapy. There was an increase in independence in the elderly who was given a modified occupational therapy with Group Psychotherapy compared to being given occupational therapy alone. It is recommended for nurses at the nursing home to get modified Occupational therapy training with Group Psychotherapy as one of the interventions in an effort to increase the independence of the elderly